Wacana kepimpinan dalam ucapan Abdullah Ahmad Badawi - Junaidi, Radiman; Zainon Hamzah, Zaitul Azma (Dewan Bahasa dan Pustaka, 2013)
This study aims to show the practices of leadership by Abdullah Ahmad Badawi as seen in the texts of his speeches at the UMNO General Assembly. Based on Fairclough’s critical discourse analysis framework. This theoretical framework exposes weighty social issues in the discourse of the speeches to explain power relations and also shows the links between economic, social, cultural and political contexts. This study also explains the meanings of words that articulate the throughts and practices of the speaker’s leadership. Abdullah Ahmad Badawi is shown to be thinking in Malay and based on Malay culture with the aim of bringing change into his leadership. The study finds that tolerance also influence his leadership practices. Abdullah Ahmad Badawi’s tolerant and transparent leadership practices are clearly shown in his speeches, which highlight his actions and efforts, while his leadership is proof of his commitment to respect other religions and cultures. In this regard, the use of the critical discourse analysis framework to analyse the political speeches of Abdullah Ahmad Badawi is a means to show that language is a way to uncover the qualities of a leader.